2007
DOI: 10.1016/j.biopsych.2007.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Frontal and Limbic Activation During Inhibitory Control Predicts Treatment Response in Major Depressive Disorder

Abstract: Background-Inhibitory control or regulatory difficulties have been explored in major depressive disorder (MDD) but typically in the context of affectively salient information. Inhibitory control is addressed specifically by using a task devoid of affectively-laden stimuli, to disentangle the effects of altered affect and altered inhibitory processes in MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
161
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(174 citation statements)
references
References 56 publications
11
161
1
1
Order By: Relevance
“…Furthermore, optimized detection of response and remission was achieved by mapping the dynamic speed of individual treatment response with a sigmoid function. Thereby, aberrant frontal and anterior cingulate activity were confirmed as important correlates of antidepressant response [6,[15][16][17]. Finally, we detected that remission was associated with higher pretreatment TPJ activity.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, optimized detection of response and remission was achieved by mapping the dynamic speed of individual treatment response with a sigmoid function. Thereby, aberrant frontal and anterior cingulate activity were confirmed as important correlates of antidepressant response [6,[15][16][17]. Finally, we detected that remission was associated with higher pretreatment TPJ activity.…”
Section: Discussionsupporting
confidence: 63%
“…Extending on this point, we might consider the present findings in the context of results for non-emotion tasks that require effortful cognition. Using a cognitive task to probe effortful inhibition, increased (rather than decreased) activation of the amygdala and regions to which it projects has been found to predict antidepressant response (Langenecker et al, 2007). In a separate study of the iSPOT-D sample, we have also observed that increased activation of the DLPFC engaged by a response inhibition task is predictive of response (Gyurak et al, 2015).…”
Section: Discussionmentioning
confidence: 68%
“…Recent reports have shown an altered emotion processing in depression compared with the healthy state concerning the perception and also the anticipation of emotional events (e.g. for reviews, see Drevets, 2001 ;Davidson et al 2002 ;Phillips et al 2003 ;Leppanen, 2006 ; for recent reports, see Keedwell et al 2005 ;Abler et al 2006 ;Johnstone et al 2007 ;Langenecker et al 2007 ; Lee et al 2007 ;Dannlowski et al 2008 ;Fales et al 2008 ;Grimm et al 2008 ;Knutson et al 2008 ;Mitterschiffthaler et al 2008). However, the direct comparison of anticipating events of known positive and negative valence with an unknown valence as a model of ' pessimistic ' expectation has not yet been performed in depressed patients.…”
Section: Introductionmentioning
confidence: 99%